Isokinetic knee strength as a predictor of cardiorespiratory responses during loaded aerobic capacity test in elite athletes - Bekir Çar; Ahmet Kurtoğlu; Özdemir Atar; Musa Türkmen; Özgür Eken; Mehmet Soyler; Monira I. Aldhahi (Scientific Reports)
Abstract This study aimed to investigate the predictive capacity of knee isokinetic strength parameters on cardiorespiratory responses during aerobic capacity test (ACT). It provides novel insights into the interplay between muscular strength and cardiorespiratory function through comparative analyses of loaded and unloaded ACT protocols in elite athletes. Thirty elite modern pentathlon athletes (age: 21.43 ± 0.77 years) underwent isokinetic knee strength assessments at angular velocities of 60°/s and 240°/s. Cardiorespiratory parameters—average breath volume (ABV), average breath frequency (ABF), auxiliary oxygen density (AOD), and heart rate (HR)—were recorded during the Bruce Protocol conducted under two conditions: unloaded and with a 10 kg loaded vest. Relationships between isokinetic strength metrics and cardiorespiratory parameters were analyzed using linear regression models. There were no significant differences in ABV, ABF, or AOD between loaded and unloaded ACT conditions (p > .05). However, HR was significantly lower during loaded ACT (p < .05). Linear regression revealed that at 60°/s, several knee strength parameters, including peak torque extension (PT-EXT), peak torque flexion (PT-FLX), total work flexion (TW-FLX), average power flexion (AP-FLX), and agonist strength (AGANT), significantly predicted ABV during loaded ACT (R2 = 0.804, p = .004). A similar pattern was observed at 240°/s, where comparable predictors explained a significant variance in ABV (R2 = 0.761, p = .012). No significant predictive relationships were identified during unloaded ACT. Isokinetic knee strength parameters significantly predict cardiorespiratory responses during loaded ACT but not during unloaded protocols. These findings suggest that isokinetic strength assessments may be a valuable tool for optimizing ACT prescription and monitoring training adaptations in elite athletes.